July 2022 Placement Ads (The Accounting Review, 2022)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for updated, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.PLACER COUNTY'S AUDITOR-CONTROLLER'S OFFICE is currently seeking a Managing Accountant. The Managing Accountant is a specialized, unclassified management position that reports directly to the Assistant Auditor-Controller and is responsible for planning, organizing, directing, and managing the activities of the General Accounting division. To apply for our exciting employment opportunity please visit: https://www.jobapscloud.com/placer/. All applications must be submitted by the final filing deadline.SAINT XAVIER UNIVERSITY, Chicago, IL, Graham School of Management invites applications for a one-year non-tenure-track Assistant Professorial Lecturer in Accounting, to begin on or about August 1, 2022. Applicants for the position must hold a Ph.D. degree (or equivalent) or ABD in Accounting, or a related field with significant research in accounting by the time of the appointment. The preferred candidate will have teaching experience and/or significant work-related experience in accounting. Please submit a letter of interest, curriculum vita, teaching statement with student evaluations if available, research statement, transcript, and names and contacts of three references through the University's website: https://www.schooljobs.com/, job number 00466. Saint Xavier University is an Equal Opportunity/Affirmative Action Employer, and actively seeks and encourages applications from minorities, women and people with disabilities.PACIFIC UNIVERSITY, College of Business at Oregon, invites applications for a full-time, tenure-track Assistant Professor of Accounting starting in Fall 2022 or Spring 2023 or earlier by arrangement. Review of applications will begin immediately. Applicants should submit a letter of interest (cover letter), curriculum vitae, and teaching statement, via Paycom: www.pacificu.edu/jobs.